IN-OUT AND NEAR. PATTERNS OF HOARDING IN PRE-, DURING- AND POST-ROMAN DACIA. THE BENEFITS OF USING A LARGE DATABASE – COIN HOARDS OF THE ROMAN EMPIRE PROJECT (CHRE) - Cristian GĂZDAC (Journal of Ancient History and Archaeology)
The present paper is presenting the benefits of using huge database covering large areas – the Roman Empire and beyond – on a long chronological segment – 1st – 5th centuries AD. As a case study was chosen the Roman province of Dacia (mainly nowadays Romania) as a territory on which the Roman coinage was documented before, during and after the Roman administration. This paper intends to point out general and specific patterns of the coin hoarding in Dacia.